2016
DOI: 10.1177/1462474516649175
|View full text |Cite
|
Sign up to set email alerts
|

Honour and respect in Danish prisons: Contesting ‘cognitive distortions’ in cognitive-behavioural programmes

Abstract: Using empirical data from prison-based cognitive-behavioural programmes, this article considers how prisoners' subcultural capital shapes their responses to demands for 'cognitive self-change'. We argue that accounts of 'respect' in the prior literature fail to capture how prisoners react to these programmes, and that a discussion of honour (and what we term 'respect plus') needs to be incorporated. The empirical material derives from four different cognitive-behavioural programme setups in three Danish prison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 44 publications
2
11
0
Order By: Relevance
“…The notion that good behaviour impacts your case is an effective regulatory practice in secure care, even though, or maybe especially, when the young people do not know what is required of them to move on (Enell, 2017). This resonates with findings among prisoners who engage in treatment and behave well to improve their chances for early release or conditions in custody (Laursen & Laws, 2016). While the disciplinary effects are evident, it is also worth observing how indefinite time opens a space, where the young people attempt to shape and thus actively engage in regaining control or abbreviate ‘stolen time’, ‘wasted time’ and time spent away from relations and activities on the outside.…”
Section: Discussionsupporting
confidence: 79%
“…The notion that good behaviour impacts your case is an effective regulatory practice in secure care, even though, or maybe especially, when the young people do not know what is required of them to move on (Enell, 2017). This resonates with findings among prisoners who engage in treatment and behave well to improve their chances for early release or conditions in custody (Laursen & Laws, 2016). While the disciplinary effects are evident, it is also worth observing how indefinite time opens a space, where the young people attempt to shape and thus actively engage in regaining control or abbreviate ‘stolen time’, ‘wasted time’ and time spent away from relations and activities on the outside.…”
Section: Discussionsupporting
confidence: 79%
“…Contextualized explanations are not in accordance with the notion of cognitive distortions, which means that context-dependent narratives are condemned as faulty thinking or a lack of responsibility. Anger Management fails to incorporate contextual experiences of violence, and the struggles and constraints of life outside and behind bars appear to resonate poorly with an individualized method of treatment (Laursen and Laws 2016).…”
Section: Contextualized Violencementioning
confidence: 99%
“…Scholars argue that treatment and care within institutions with a mandate to punish result in “contradictory, uneven and diffuse strategies of governance” (Pollack 2009, 126; see also Svensson 2002). Previous research on prison-based cognitive-behavioral programs tends to inquire into whether they work or not (e.g., Lipsey, Landenberger, and Wilson 2007; Porporino, Fabiano, and Robinson 1991; Tong and Farrington 2006; Wilson, Bouffard, and MacKenzie 2005), how the prisoners experience the programs (e.g., Cox 2011; Fox 1999a, 1999b; Hannah-Moffat 2000; Laursen and Laws 2016; Laursen 2017; McKim 2008; Perry 2013), and how such programs are embedded in larger societal discourses and transformations (i.e., Andersson 2004; Kemshall 2002; Kendall 2011; Lacombe 2008; Nilsson 2013; Robinson 2008; Rose 2000). Cognitive-behavioral programs, being the sine qua non of prison-based rehabilitation, requires continued scholarly attention on how prisoners experience such interventions, how treatment affects their sense of self, and whether treatment improves prisoners’ resources for coping with micro- and meso-level challenges.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the participants in cognitive behavioural programmes recogniseand are playing withboth the values of their social and ethnic origins and those to which they have to conform in order to satisfy the programme instructor, the programme requirements and, in a larger scheme, the prison. The participants often draw upon a street-based, subcultural capital (Laursen & Laws 2016), which was also on display when one of the participants suggested that 'you should drink a beer when you are upset'. This suggestion seemed sound enough, but another participant quickly answered 'yeah, but then you end up getting arrested because you smashed someone in town'.…”
Section: Humour In the Shape Of Soft Resistance And Code-switchingmentioning
confidence: 99%
“…Ahmad toys with the instructor and the exercise by humorously suggesting that he would put on a facial mask (a 'feminine' recreational activity) while listening to Tupac (a 'masculine' or street-based appropriation of 'proper' relaxation). Listening to rap music is not deemed a proper or constructive relaxation activity by some of the cognitive behavioural instructors (see Laursen & Laws 2016), but Ahmad seems to recognize the instructors expectations (that he will choose a 'wrong' type of relaxationlistening to Tupac) while he simultaneously suggests a 'decent' relaxation activity. In an attempt to redirect the discussion, the instructor then said that he 'reads a novel and listens to Frank Sinatra' when he is upset.…”
Section: Humour In the Shape Of Soft Resistance And Code-switchingmentioning
confidence: 99%